MIND MAPPING: A BRAIN-BASED WRITING STRATEGY - Ningrum, Ary Setya Budhi (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2011)
In EFL context, it is believed that developing writing skills is more complicated than developing other language skills. In order to be able to write well, the foreign language learners need to be equipped with early and continued writing experiences. Thus, the teacher’s task to develop the students’ writing skill is more complicated than the other skills. One of the most current issues to deal with such phenomena is to ferret out the writing strategy that is able to enhance the students’ writing ability as well as to reinforce their critical thinking in writing by maximizing the use of both sides of the brain (the left and the right hemispheres). In response to such issues, this paper takes into account mind mapping as a strategy in writing and elaborates the theoretical review of mind mapping for better understanding.Keywords: Mind Mapping, Writing